2017
DOI: 10.18203/2320-6012.ijrms20170155
|View full text |Cite
|
Sign up to set email alerts
|

Functional and radiological outcome in distal radius fractures treated with locking compression plate

Abstract: Background: Fractures of distal end of radius are one of the most common skeletal injuries encountered in orthopaedics. There are various modalities for treatment like close reduction and cast application, external fixators, ORIF with plate etc. CR and cast application or K-wire fixation, external fixation is associated with immobilisation, wrist stiffness, loss of reduction postoperatively. So we performed volar plating for distal end radius fractures and calculated its results.Methods: We performed ORIF with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
7
7
1
Order By: Relevance
“…According to MAYO wrist score Agarwala et al reported excellent/good result in 88% and satisfactory result in 12% of patients and similar results were obtained in the study done by Chavhan et al [14,18] Results obtained in the present study are similar & comparable to the results reported in the literature in terms of union, anatomical parameters and functions with special feature of minimal complications.…”
Section: Discussionsupporting
confidence: 91%
“…According to MAYO wrist score Agarwala et al reported excellent/good result in 88% and satisfactory result in 12% of patients and similar results were obtained in the study done by Chavhan et al [14,18] Results obtained in the present study are similar & comparable to the results reported in the literature in terms of union, anatomical parameters and functions with special feature of minimal complications.…”
Section: Discussionsupporting
confidence: 91%
“…Agarwal et al [12] in their study reported similar pattern. Chauhan AN et al [7] in their study reported excellent results in 45.7%, good results in 42.95% and satisfactory results in 11.4% which were different from the present study findings. This may be due to the fact that Mayo score system was not used in theirstudy.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study mean age of the patients was found to be 40.03 years. Chauhan et al [7] reported mean age of 42.8 years, Pratap et al [8] reported mean age of 36.6 years, Jagdev SS [9] reported mean age of 43.2 years. In the present study 55.82% of males and 55.56% of females were in the 40-60 years age group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the 9 case managed with the K-wiring the mean Lidstrom scores were 3.66, 3, 2.55, 3.11 respectively (P-value 0.041). [5] .…”
Section: Figmentioning
confidence: 99%